Facing the Danger Zone: The Use of Ultrasound to Distinguish Cellulitis from Abscess in Facial Infections. (16th January 2014) - Lewis, Dywanda L.; Butts, Christine J.; Moreno-Walton, Lisa
Abstract : Physical exam alone is often insufficient to determine whether or not cellulitis is accompanied by an abscess. Bedside ultrasound can be a valuable tool in ruling out suspected abscess by allowing direct visualization of a fluid collection. The proximity of the infection to adjacent structures can also be determined, thus aiding clinical decision making. Patients with cellulitis near the eye and nose are of particular concern due to the adjacent facial structures and the anatomy of the venous drainage. Accurately determining the presence or absence of an associated abscess in these patients is a crucial step in treatment planning. The purpose of this report is to (1) emphasize the benefits of bedside ultrasound when used in conjunction with the physical exam to rule out abscess; (2) demonstrate the utility of bedside ultrasound in planning a treatment strategy for soft tissue infection; (3) depict an instance where ultrasound detected an abscess when computed tomography (CT) scan did not.